Serological detection of West Nile virus in horses and chicken from Pantanal, Brazil - Melandri, Vanessa (2012)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Diptera. Rio de Janeiro, RJ, Brasil.